2020
DOI: 10.1177/1464419320917235
|View full text |Cite
|
Sign up to set email alerts
|

Vibration analysis of the axle bearings considering the combined errors for a high-speed train

Abstract: Axle bearings are critical elements of high-speed trains. Although the quality and precision of axle bearings have been significantly improved, the manufacturing errors, such as the roundness and waviness errors, cannot be eliminated during their manufacturing processes. The axle bearings with the roundness and waviness errors have great influences on vibration performances of the high-speed trains. To obtain an in-depth understanding of the vibrations caused by the axle bearing with the combined errors consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Meanwhile, the simulated time interval between impulse C1 and C2, D1 and D2 are approximately 6.1 ms, equaling to 1/f BPFI . The time interval between D1 and C2 is approximately 4.6 ms, and the time difference relationship given by Igarashi et al 5 for ball bearing with two defects on inner raceway are shown in equations (30) and (31),…”
Section: Defects On Inner Raceway Surfacementioning
confidence: 92%
See 2 more Smart Citations
“…Meanwhile, the simulated time interval between impulse C1 and C2, D1 and D2 are approximately 6.1 ms, equaling to 1/f BPFI . The time interval between D1 and C2 is approximately 4.6 ms, and the time difference relationship given by Igarashi et al 5 for ball bearing with two defects on inner raceway are shown in equations (30) and (31),…”
Section: Defects On Inner Raceway Surfacementioning
confidence: 92%
“…Liu et al. 31 conducted an improved analytical model for a high-speed train considering the axle bearings with combined roundness and waviness errors. The ADAMS model 32 could be used to simulate complex bearing defects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Track geometry degradation can have a negative impact on passenger comfort and safety. Moreover, the track geometry degradation can significantly affect the working performance, and noise, vibration, and harshness characteristics of the whole train system [5]. Therefore, effective track maintenance is essential to prevent these negative effects.…”
Section: Introductionmentioning
confidence: 99%
“…Dipen and Patel [12] established a dynamic model to study the vibration responses of ball bearings with obvious raceway waviness. Liu et al [13,14] introduced a displacement excitation model to study the coupling errors including the waviness and roundness of both raceways and balls. The effects of the order and amplitudes of the coupling errors on the vibrations of ball bearings were studied.…”
Section: Introductionmentioning
confidence: 99%